Combining donor derived cell free DNA and gene expression profiling for non‐invasive surveillance after heart transplantation. Issue 3 (23rd May 2022) - Henricksen, Erik J.; Moayedi, Yasbanoo; Purewal, Saira; Twiggs, Julien Valverde; Waddell, Kian; Luikart, Helen; Han, Jiho; Feng, Kent; Wayda, Brian; Lee, Roy; Shudo, Yasuhiro; Jimenez, Shirin; et al.
Abstract: Background: Donor‐derived cell free DNA (dd‐cfDNA) and gene expression profiling (GEP) offer noninvasive alternatives to rejection surveillance after heart transplantation; however, there is little evidence on the paired use of GEP and dd‐cfDNA for rejection surveillance. Methods: A single center, retrospective analysis of adult heart transplant recipients. A GEP cohort, transplanted from January 1, 2015 through December 31, 2017 and eligible for rejection surveillance with GEP was compared to a paired testing cohort, transplanted July 1, 2018 through June 30, 2020, with surveillance from both dd‐cfDNA and GEP. The primary outcomes were survival and rejection‐free survival at 1 year post‐transplant. Results: In total 159 patients were included, 95 in the GEP and 64 in the paired testing group. There were no differences in baseline characteristics, except for less use of induction in the paired testing group (65.6%) compared to the GEP group (98.9%), P  < .01. At 1‐year, there were no differences between the paired testing and GEP groups in survival (98.4% vs. 94.7%, P  = .23) or rejection‐free survival (81.3% vs. 73.7% P  = .28). Conclusions: Compared to post‐transplant rejection surveillance with GEP alone, pairing dd‐cfDNA and GEP testing was associated with similar survival and rejection‐free survival at 1 year while requiring significantly fewer biopsies.